Accelerating Green Campus Policies: Efforts to Mitigate Environmental Degradation and Transform Sustainable Governance - Devid Prianata (AMUYA: JOURNAL OF MANAGEMENT, 2026)
This policy paper examines the urgency of strengthening regulations related to the implementation of a Green Campus at the Palangka Raya State Christian Institute, which currently faces serious challenges in the form of environmental degradation and the deterioration of public spaces. The main issues identified include the loss of water absorption areas due to land conversion into physical structures, the low effectiveness of vegetation maintenance, and waste management that has not yet been integrated into a circular system. Using a policy analysis method that includes identifying the root causes through the Urgency, Seriousness, Growth (USG) technique, this paper evaluates various managerial obstacles hindering the creation of a sustainable educational ecosystem. The review process was conducted by comparing several policy alternatives, in which the issuance of a Minister of Religious Affairs Regulation regarding green campus guidelines was assessed as the most effective solution to provide a binding legal framework for all State Religious Universities. This approach was chosen because it effectively integrates physical infrastructure management standards with environmental conservation needs while fostering innovation in campus community participation. The strategic recommendations proposed include the development of comprehensive regulations mandating a minimum of thirty percent green open space, the standardization of pedestrian-friendly facilities, and the establishment of an integrated waste management system. The implementation of this policy is projected not only to mitigate local temperature increases on campus but also to transform institutional governance into a more accountable, efficient, and globally competitive system in support of achieving sustainable development goals. Through these policy measures, the transformation of the campus ecosystem into a healthy, shaded, and productive livable space can be accelerated to realize environmentally conscious higher education standards in the long term.